Saint Augustine on the role of the Holy Spirit in judgment - Haflidson, Ronald Keith (The University of Edinburgh, 2014)
In On Christian Teaching, Saint Augustine writes, “Just and holy living depends on being a good judge of things.” This brief sentence lucidly articulates the importance that judgment plays in Augustine’s thought. This thesis is the first full-length study of how he understands the distinct role of the Holy Spirit in judgment. I argue that judgment denotes both the discernment of a thing’s nature and evaluation of it; and we become good judges only as we are re-ordered by the love which is, in Augustine’s favourite pneumatological verse, “poured into our hearts by the Holy Spirit” (Romans 5:5). I analyse this transformative work of the Spirit according to two broad categories: first, the Spirit re-orders our relation to creation principally by uniting us to the Word, the second person of the Trinity, in whom all things are created, and so we are able to discern a thing’s nature and evaluate it according to God’s purposes in creation; and, second, the Spirit re-orders our relation to time, as we patiently endure this troublous life as pilgrims hoping for eternal Sabbath rest; within this eschatological horizon situated in the age between Christ’s first coming and his return, we restrain ourselves from making both unfounded and unnecessary judgments as we defer to God’s final judgement. This thesis is divided into two parts. In the first part, on the “theory” of judgment, I explicate the consistent relation throughout Augustine’s corpus between pneumatology, judgment and ethics (chapter one). I then proceed to trace out his account of how the gift of the Spirit’s love perfects our judgment by re-ordering our relation to creation, and, conversely, how lust distorts it. A right relation to creation turns on taking up our middle place: below God, next to our neighbours, and above nature (chapter two). In the second part, on the “practice” of judgment, I focus first on other-judgment, especially the role of mercy (chapter three), and then in the fourth and final chapter I turn to self-judgment, including a lengthy consideration of the nature and role of conscience (chapter four). For Augustine, then, it is only by the Spirit’s love that we are made good judges, and, simultaneously, it is only when we are good judges that our love conforms to the truth both of God’s good creation and of our in-between age.
Keywords: Augustine; Holy Spirit; judgment; Trinity; ethics